Pengaruh Metode Inkuiri Berbasis Eksperimen Terhadap Hasil Belajar IPA Kelas IV di MI Tahassus Ma’arif NU Prapagkidul Kecamatan Pituruh Kabupaten Purworejo - Siti Samchaturochmah; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This research aims to determine the implementation and influence of experiment-based inquiry methods on science learning outcomes of fourth-grade students at MI Tahassus Ma'arif NU Prapagkidul. This study adopts a quantitative approach with an experimental research design. The subjects of the study were 25 fourth-grade students at MI Tahassus Ma'arif NU Prapagkidul. Data were collected through interviews, observations, and tests. The data analysis technique used in this research was the Paired Sample T-Test through SPSS 25.0 software. The results of the study indicate that the implementation of experiment-based inquiry methods is conducted through six steps: presenting the problem, formulating hypotheses, designing experiments, conducting experiments, analyzing data, and drawing conclusions. Furthermore, the influence of experiment-based inquiry methods is supported by the hypothesis test results, which obtained a significance value (sig) of 0.00, indicating that the null hypothesis (Ho) is rejected. Therefore, it can be concluded that Ho is rejected, and the alternative hypothesis (Ha) is accepted, which states that "There is an influence of experiment-based inquiry methods on the science learning outcomes of fourth-grade students at MI Tahassus Ma'arif NU.